A CORRELATION ANALYSIS OF LEARNING ORGANIZATION AND CHANGE MANAGEMENT: IS IT A STRATEGY TO HAVE A COMPETITIVE ADVANTAGE IN YOUR ORGANIZATION? - Parameswaran, Hima (PEOPLE: International Journal of Social Sciences, 2020)
For an organization to be competitive, employee involvement plays a significant role. As human wants and needs are always changing, it necessitates new products and services in the market. When it comes to external triggers; social, political, economic, and technological changes impact organizational policies and processes. To update these elements, organizations must have a learning culture by adopting a strategic move in its structure. A mixed-approach (theories and survey/interview) study with an investigation on change management and learning organization in selected industrial companies in the UAE, with a sample size of 400, aids to find the relationship between learning organization, change management, and competitiveness. The quantitative and qualitative analysis confirms the significance level of related dependent variables and the acceptance of hypothesis tests. Hence, organizations can utilize the model, strategic learning-change bundle that is crafted from this study towards its competitive advantage. Moreover, this study can further be analyzed with other change management variables as change is a continuous process.